2018
DOI: 10.30848/pjb2019-1(11)
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cattle manure on the content of major minerals and nitrogen uptake from 15n isotope-labeled ammonium sulphate fertilizer in maize (Zea mays L.) plants

Abstract: Jordan Valley is considered as one of the main intensified irrigated agricultural areas in Jordan with high use of fertilizers especially of nitrogen source which lead to increased ground water pollution with nitrate. A field trial was conducted at the National Agricultural Research Center in Jordan Valley, North West Amman. Six soil treatments with organic cattle manure at the following rates were applied in summer 2014 and 2015: 0 (control), 8, 12, 16 and 20 tons ha −1. Treatments were arranged in a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, many studies concluded that low productivity is primarily related to management practices in dryland agriculture [50][51][52][53][54][55][56]. In addition, research has demonstrated substantial linkages between temperature, fertilizer applications, plant populations and planting dates [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Mineralization Of Organic Phosphorousmentioning
confidence: 99%
“…On the other hand, many studies concluded that low productivity is primarily related to management practices in dryland agriculture [50][51][52][53][54][55][56]. In addition, research has demonstrated substantial linkages between temperature, fertilizer applications, plant populations and planting dates [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Mineralization Of Organic Phosphorousmentioning
confidence: 99%
“…Organic fertilizer encompasses a diverse range of organic amendments applied to soils, with exceptions made for direct excreta deposition by grazing animals. This category includes compost, wood chips, biochar, animal feces, hay, husk, and geotextile (Al-Taey et al, 2019; Hani et al, 2019;Al Tawaha et al, 2021;). Organic or natural fertilizers originate from natural sources, containing at least one essential nutrient vital for plant nourishment (Singh et al, 2023a,b,c; The Effect of Compost Tea on Some Growth and Yield Parameters and Soil Chemical Properties of Greenhouse Tomato (Solanum lycopersicum L.) Samih Abubaker 1 , Issam Qrunfleh 1 , Mohamad Shatnawi 3 , Tarek G. Ammari 2 , Hazem Hasan 1 , Abdel Rahman M. Al Tawaha 4* al., 2024; Singh et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…e maize crop has also been shown to accrue various metals, for example, cadmium [19]. Maize is also considered a metal tolerant crop [20].…”
Section: Introductionmentioning
confidence: 99%